Bienzymatic fluorescence detection based on paraoxonase and laccase on anthracene-sequestered polyamic acid films: A novel approach for inhibition-based sensors - Esen, Elif; Yazgan, İdris; Odaci Demirkol, Dilek (Elsevier BV, 2020)
Abstract A fluorescence assay based on paraoxonase (PO) and laccase (Lac) immobilized on anthracene-sequestered polyamic acid films is now being reported for the first time for ciprofloxacin (CFx) detection. In enzymatic reaction, PO converts phenyl acetate (PA) to acetic acid and phenol. The formed phenol is further oxidized by laccase using oxygen as a co-substrate. For indirectly fluorescence measurements of PA hydrolysis, increased fluorescence intensity was measured after oxygen consumption by laccase. This is because oxygen is quencher of anthracene (Ant) incorporated in the sequestered poly(amic) acid (PAA) film. The detection mechanism was based on inhibition of PO activity by CFx. Using PAA provided the advantage of controlling the film thickness. Firstly, morphology of PAA-Ant polymeric film was characterized by scanning electron microcopy (SEM) and the success of PO-Lac immobilization on PAA-Ant was proven by SEM plus Energy-dispersive X-ray spectroscopy (SEM-EDX) and fluorescence measurements. Then Ant-PAA/PO/Lac is calibrated for PA and CFx without any interfering of some potential interferences. All results make it a promising tool for monitoring CFx at minute levels in samples.
Keywords: Antibiotic detection; Inhibition-based sensing; Paraoxonase; Laccase